Seminoma Klasik pada Laki-laki Usia 72 Tahun - Singgih, Nicholas Andrian; Lionardi, Stevan Kristian; Mintardi, Mintardi (PT Kalbe Farma Tbk., 2024)
Testicular cancer accounts for 1% of all malignancies and 5% of urological-related neoplasms; most commonly in young males aged 15-40 years, seminoma is the most common subtype (50%-60%). A 72-year-old patient with increasing right scrotum size since 3 years ago. A right testicular tumor was found. Trans-scrotal radical orchiectomy was done as the definitive treatment. The result of the histopathological examination was a classic seminoma pT1. GCT is a testicular cancer uncommonly diagnosed in the elderly. A better prognosis is achieved through early diagnosis and appropriate treatment.